Preparation of SiC from acid‐leached coal gangue by carbothermal reduction. Issue 3 (17th January 2018) - Li, Fachuang; Guo, Zhanyong; Su, Guang; Guo, Chaobo; Sun, Guojin; Zhu, Xinlin
Abstract: For the comprehensive utilization of coal gangue, acid‐leached coal gangue was used as silicon source and part of carbon source, low ash anthracite and degreasing cotton were added respectively as supplementary carbon source, SiC and SiC fiber were prepared by carbothermal reduction method accordingly. The results show that the main components in leached coal gangue are amorphous SiO2 and carbon, which are suitable for the synthesis of SiC as raw materials. The synthesis temperature and holding time have important influence on the synthesis of SiC, and the optimum synthesis parameters for SiC are at 1550°C for 4 hours; under this condition, the yield of SiC is 78.27%, and the specific surface area is 6750 cm 2 /g. The results show that the resulting products are essentially composed of β‐SiC with a minor amount of α‐SiC. Besides, based on the carbon fiber transformation method, SiC fiber was prepared by using leached coal gangue and degreasing cotton as raw materials. Therefore, it can be concluded that leached coal gangue is a very effective and inexpensive source for preparing SiC, and more importantly, this work has important economic and social significance to realize waste recycling and control pollution.